The influence of stereotype threat on immigrants: review and meta-analysis - Appel, Markus; Weber, Silvana; Kronberger, Nicole (Frontiers in Psychology, 2015)
In many regions around the world students with certain immigrant backgrounds underachieve in educational settings. This paper provides a review and meta-analysis on one potential source of the immigrant achievement gap: stereotype threat, a situational predicament that may prevent students to perform up to their full abilities. A meta-analysis of 19 experiments suggests an overall mean effect size of .63 (random effects model) in support of stereotype threat theory. The results are complemented by moderator analyses with regard to circulation (published or unpublished research), cultural context (US vs. Europe), age of immigrants, type of stereotype threat manipulation, dependent measures, and means for identification of immigrant status; evidence on the role of ethnic identity strength is reviewed. Theoretical and practical implications of the findings are discussed.